Mathematical Epistemic Beliefs: Through the Gender Lens - Trakulphadetkrai, Natthapoj Vincent (Frontiers in Education, 2022)
This large survey study set out to ascertain whether gender differences in teachers’ mathematical epistemic beliefs exist, and the extent to which teachers’ gender as well as their teaching experience level, education level, and socio-economic setting of the schools can predict these beliefs. Specifically, the study examined teachers’ beliefs concerning the structure, stability, and source of mathematical knowledge. This is crucial given that previous research have demonstrated the potential role of teachers’ mathematical epistemic beliefs in shaping their mathematics teaching, and hence their students’ mathematics learning outcomes and perceptions of the subject. The current study drew on survey data collected from 745 primary teachers using items from the Thai Teachers’ Mathematics Education-related Beliefs (TTMEB) questionnaire. The data were analysed using Independent-samples t-test and multiple regression. The findings reveal a very limited to no effect of gender on teachers’ mathematical epistemic beliefs, and also alert us to the fact that when it comes to exploring factors that shape one’s beliefs, their exogenous characteristics, such as the socio-economic setting of where they live and work, should too be taken into account. Overall, the study helps to dispel any myths about gender differences in the way male and female teachers perceive mathematics, specifically the nature of mathematical knowledge.